Remote Wind Turbine Inspections: Exploring the Potential of Multimodal Drones - Ahmed Omara; Adel Nasser; Ahmad Alsayed; Mostafa R. A. Nabawy (Drones)
With the ever-increasing demand for harvesting wind energy, the inspection of its associated infrastructures, particularly turbines, has become essential to ensure continued and sustainable operations. With these inspections being hazardous to human operators, time-consuming and expensive, the door was opened for drone solutions to offer a more effective alternative. However, drones also come with their own issues, such as communication, maintenance and the personnel needed to operate them. A multimodal approach to this problem thus has the potential to provide a combined solution where a single platform can perform all inspection operations required for wind turbine structures. This paper reviews the current approaches and technologies used in wind turbine inspections together with a multitude of multimodal designs that are surveyed to assess their potential for this application. Rotor-based designs demonstrate simpler and more efficient means to conduct such missions, whereas bio-inspired designs allow greater flexibility and more accurate locomotion. Whilst each of these design categories comes with different trade-offs, both should be considered for an effective hybrid design to create a more optimal system. Finally, the use of sensor fusion within techniques such as GPS and LiDAR SLAM enables high navigation performances while simultaneously utilising these sensors to conduct the inspection tasks.